Islam, Nationalism and Democracy: A Dialoguewith Dr. Anwar Haryono - Prasetyo, Hendro (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
This article contains an interview on Islam, Nationalism, and Democracy with Dr. Anwar Haryono.We would like to discuss the situation of Islam and Muslim in New Order Indonesia. To be more specific perhaps, we would like to begin with something rather controversial i.e the coming to power of the New Order goverment. This goverment has set up new policies on Islam, which are different from such policies employed by the previous goverment. REsponding to New Order policies, some Muslim prefer to adobt the so-called